Improving Basic English Skills in Health Workers, Especially in the Medical Records Section at the Kuranji Health Center, Padang City - Nila Mayasari; Syamsul Kamal (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Socialization on training in improving basic English skills among community health center staff, especially in the RM section in the admissions section, was carried out at Kuranji Padang Community Health Center, which aims to improve pronunciation skills and mastery of basic English using drilling, listening, role play and game methods. English language training using this method is used so that community health center officers can train basic English skills in medical records science in particular. This training uses a persuasive method which is a method applied in the process of improving skills. Before carrying out English language training using this method, field observations were carried out, namely by observing and asking questions to several community health center staff.